Role Of Dentist And Nurse In Antifungal Resistance In Oral Candidiasis: Mechanisms And Clinical Implications (Journal of Namibian Studies : History Politics Culture, 2022)
Antifungal resistance in oral candidiasis presents a formidable challenge in clinical practice, jeopardizing treatment efficacy and patient outcomes. This article delineates the multifaceted mechanisms driving antifungal resistance in Candida species associated with oral candidiasis and explores its clinical ramifications. Key mechanisms include target alterations, efflux pump overexpression, biofilm formation, adaptive stress responses, and sterol biosynthesis pathway alterations. Clinical implications encompass treatment failure, increased morbidity, cross-resistance, the imperative for surveillance and resistance monitoring, and the urgency for alternative therapies. Understanding these mechanisms is pivotal for devising effective treatment strategies and mitigating the escalating threat of antifungal resistance.